2013
DOI: 10.4161/psb.24260
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid and salicylic acid activate a common defense system in rice

Abstract: Jasmonic acid (JA) and salicylic acid (SA) play important roles in plant defense systems. JA and SA signaling pathways interact antagonistically in dicotyledonous plants, but, the status of crosstalk between JA and SA signaling is unknown in monocots. Our rice microarray analysis showed that more than half of the genes upregulated by the SA analog BTH are also upregulated by JA, suggesting that a major portion of the SA-upregulated genes are regulated by JA-dependent signaling in rice. A common defense system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(110 citation statements)
references
References 15 publications
3
106
0
1
Order By: Relevance
“…Supporting this concept, mounting evidence suggests that although SA-JA antagonism is conserved in rice, positive relationships between both pathways might prevail . Most conspicuously, recent microarray studies showed that unlike in Arabidopsis, more than half of all BTH-or SA-upregulated rice genes are also induced by JA (Garg et al, 2012;Tamaoki et al, 2013). Moreover, many rice mutant and transgenic lines display simultaneously enhanced SA and JA signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this concept, mounting evidence suggests that although SA-JA antagonism is conserved in rice, positive relationships between both pathways might prevail . Most conspicuously, recent microarray studies showed that unlike in Arabidopsis, more than half of all BTH-or SA-upregulated rice genes are also induced by JA (Garg et al, 2012;Tamaoki et al, 2013). Moreover, many rice mutant and transgenic lines display simultaneously enhanced SA and JA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent findings propose a conceptually different model for rice defense signaling that challenges the widely accepted dichotomy between the effectiveness of the SA and JA pathways and the overall infection biology of the invading pathogen (Yamada et al, 2012;De Vleesschauwer et al, 2013Riemann et al, 2013;Taniguchi et al, 2014). Perhaps most conspicuously, synergistic SA-JA interactions seem to prevail in rice and the two hormones are hypothesized to feed into a common defense pathway that can be effective against both hemibiotrophic and necrotrophic rice pathogens Tamaoki et al, 2013).…”
mentioning
confidence: 98%
“…Therefore, suppression of miR319-mediated JA signaling may be a 465 counter defense mechanism that is conserved among many plant/pathogen systems, which is 466 worthy of more attention. 467 Despite multiple observations suggesting that the JA signaling pathway is a potent 468 defense machinery against many pathogens (including M. oryzae) (Mei et al 2006, Thaler, 469 Humphrey et al 2012, Tamaoki, Seo et al 2013, Zhang, Ding et al 2016, the detailed 470 molecular mechanism regarding how this regulation is carried out, and how JA signaling is 471 maneuvered in the interaction between rice and the blast pathogen, is not clear. Our results 472 showed that in miR319b-OE rice, key JA synthesis components, such as OsPLDα1, OsLOX2,473 and OsLOX5, were specifically suppressed ( Figure 6).…”
Section: Guy11 Infection Induces Mir319b and Inhibits Ja-mediated Defmentioning
confidence: 99%
“…Taken together, the co-occurrence between cellular 298 H 2 O 2 levels and the in vivo OsTCP21 expression levels suggests an association of this gene 299 with the early immune response against the blast disease in rice. 300 301 miR319 impedes JA synthesis and signaling elicited by M. oryzae infection 302 JA is a phytohormone that plays a critical role in defense responses against necrotrophic 303 and hemibiotrophic pathogens (Thaler, Humphrey et al 2012, Tamaoki, Seo et al 2013, 304 Zhang, Ding et al 2016. It has been reported that in both Arabidopsis and rice, some TCP 305 transcription factors are involved in the JA signaling pathway (Schommer, Palatnik et al 2008, 306 Zhang, Ding et al 2016.…”
Section: Avr1-co39mentioning
confidence: 99%
See 1 more Smart Citation